Analisis Manajemen Sumber Daya Manusia di Sekolah Dasar Islam Terpadu - Antariksa, Walid Fajar (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Integrated Islamic Primary School (SDIT) is an educational institution that is increasingly in demand by society because of its good quality. The quality of educational institutions is certainly influenced by the management of human resources. The purpose of this research is to analyze human resource management in SDIT. The location of this research is at SDIT Insan Permata in Malang City. The method used in this research is descriptive qualitative method. Data were collected by observation methods, interviews and by reviewing relevant documents. The results showed that SDIT Insan Permata in general has a good human resource management system, ranging from recruitment system, competency development, performance appraisal to employee compensation. Nevertheless, there are still some that need to be improved, such as the operational system procedures need to be documented and controlled well, the recruitment path that needs to be improved and the high turn over of employees that need to be anticipated